PENGARUH PERANGKAP WARNA BERPEREKAT TERHADAP HAMA CAPSIDE (Cyrtopeltis tenuis Reut) (Hemiptera : Miridae) PADA TANAMAN TEMBAKAU (Nicotiana tabacum L.) - Stevi Windy Sihombing; Yuswani Pangestiningsih; Mena Uly Tarigan (Universitas Sumatera Utara, 2013)
The influence of adhesive colored trap on capside pest (Cyrtopeltis tenuis Reut.)(Hemiptera:Miridae) in tobacco plant (Nicotiana tabacum L.). The is research was to find out theeffectiveness of the adhesive colored trap on capside pest (Cyrtopeltis tenuis Reut.)(Hemiptera:Miridae) in tobacco plant (Nicotiana tabacum L.) in the field. The purpose of this studyconducted at Kelambir V Helvetia Estate of PTPN II from May to June 2012. The methods used inthis study were Non-Factorial Group Randomized Design (RAK) with 7 treatment, and 3replications: W0 (controlled/ transparent), W1 (green colored traps), W2 (light red colored Trap), W3(white colored traps) W4 (yellow colored traps) W5 (blue colored Traps), W6 (red colored traps). Theresult of this study showed that the highest pest population caught by yellow colored trap was 53.00and the lowest pest population was 33.33 which were caught by light red colored trap. The lowestattact intencity percentage was 28.53% found in the yellow colored trap, and the highest was34.86% found in the blue colored trap.Keywords: Cyrtopeltis tenuis Reut, Colored Trap, Nicotiana tabacum L.